2003
DOI: 10.1099/mic.0.26034-0
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of an extradiol dioxygenase involved in tetralin biodegradation identifies residues important for activity or substrate specificity

Abstract: The sequence of the extradiol dioxygenase ThnC, involved in tetralin biodegradation, was aligned with other extradiol dioxygenases involved in biodegradation of polycyclic compounds, and a three-dimensional model of ThnC, based on the structure of the previously crystallized 2,3-dihydroxybiphenyl dioxygenase from Burkholderia fungorum LB400, was built. In order to assess the functional importance of some non-active-site residues whose relevance could not be established by structural information, a number of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Such a difference is of the same order of magnitude as that previously described for the site-directed mutants of an extradiol dioxygenase involved in tetralin degradation, for which turnover numbers could be increased by a factor of three compared to the wild-type (Andujar & Santero, 2003).…”
Section: Resultssupporting
confidence: 67%
“…Such a difference is of the same order of magnitude as that previously described for the site-directed mutants of an extradiol dioxygenase involved in tetralin degradation, for which turnover numbers could be increased by a factor of three compared to the wild-type (Andujar & Santero, 2003).…”
Section: Resultssupporting
confidence: 67%
“…The 2.1 Å crystal structure of Memo revealed that it is structurally homologous to a class of non-heme iron dioxygenases that are mainly found in bacteria (Andujar and Santero, 2003); however, we were unable to detect metal binding or enzymatic activity (Qiu et al, 2008). To gain more insight into Memo function, we used the yeast two-hybrid (YTH) approach to identify Memo-interacting proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Genes required for tetralin biodegradation ( Fig. 1) have been sequenced, and the functions of their gene products have been characterized to elucidate the biodegradation pathway (1,2,(16)(17)(18)27). As observed for other aromatic compounds, degradation of tetralin is initiated by dioxygenation of the aromatic ring, a reaction requiring oxygen and an external electron supply, which is catalyzed by the tetralin dioxygenase enzymatic complex encoded by four thnA genes (27) (Fig.…”
mentioning
confidence: 99%